Development of E-worksheet of Coordination System in Human Based on Learning Cycle 7E to Improve Critical Thinking Ability and Student Motivation - Shesilya; Suyitno Aloysius (Postgraduate, University of Mataram, 2023)
Nowadays, the ability to think critically and motivation in learning is something that must be owned by students. One of the learning models that can improve both is learning cycle 7E combined with e-worksheet. The purpose of this research is to develop e-worksheet based on learning cycle 7E to improve critical thinking skills and learning motivation of grade XI high school students as seen from the results of feasibility and practicality tests. This research is a Research and Development (R&D) study with the ADDIE model which is applied until the development stage only. The feasibility of the product was assessed by one material expert lecturer and one media expert lecturer and the practicality of the product was assessed by 5 biology teachers. The results obtained based on the product quality assessment, obtained a value from a material expert lecturer with an ideal percentage of 83.9% in the feasible category, a media expert of 83.3% which is in the feasible category, and the results of the practicality test by the teacher obtained an average ideal percentage of 94.5%. Therefore, e-worksheet based on learning cycle 7E can be used to improve critical thinking skills and student learning motivation.